Preliminary evaluation of foetal liver volume by three-dimensional ultrasound in women with gestational diabetes mellitus - Ilhan, Gulsah; Gultekin, Huseyin; Kubat, Ayca; Karasu, AYŞE FİLİZ; GÖKMEN KARASU, AYŞE FİLİZ; Gungor, Emre Sinan; Zebitay, Galip Ali; Atmaca, Fatma Ferda Verit (My University, 2018)
The aim of the study was to assess the standard foetal biometric measurements and foetal liver volume (FLV) in pregnancies complicated by gestational diabetes mellitus (GDM) at the time of GDM screening and to compare the results with foetuses in normal pregnancies. Ninety-seven pregnant women with normal singleton uncomplicated pregnancies between 24 and 28 weeks of gestation were allocated into GDM (+) (n: 33) and GDM (-) (n: 64) groups based on their 75 g oral glucose tolerance test results. Foetal biometric measurements and FLV measurements of the groups were compared. Although there were no significant differences in the standard biometric measurements between the two groups, FLV was significantly higher in the women with GDM (p < .01). The ROC analysis implied that with a cut-off value of FLV of 32.72 cm(3) for GDM prediction, the sensitivity was 78.8% and specificity was 56.3%. We suggest that FLV measurements during the second-trimester ultrasound scanning may be a tool for the prediction of GDM in the obstetric population.